Diseases of minorities? - Rivas Muñoz, Favio (Acta Bioethica, 2010)
Pandemic recent threats have uncover that, even being more difficult and unknown, the problems that risk health at international level can be controlled quickly and effectively, that is, having little technical and scientific development, human resources or money are not an obstacle to give an appropriate response. Lastly, the key of success in this matter is not found in techniques or science and the basic reason for global unequal health scene perhaps is found in the exclusion of populations considered simply unnecessary from the market and its regulations perspective, or also pointed out as guilty of their maladies because of their own culture. The present study tries to show that public health is a matter of business more than science, politics or ethics.